2016
DOI: 10.5456/wpll.18.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Retention, Understanding Attrition: A Prospective Study of Foundation Year Students

Abstract: The aim of this study was to evaluate two psychometric tools for identifying students at risk of failing to progress from a Foundation Year (FY) programme, a preparatory programme for those without the qualifications to enrol directly on to an undergraduate degree. Students from four FY programmes across two UK universities were invited to complete the survey at the start of the academic year (Time-1) and again towards the end of the FY (Time-2). The survey comprised the Academic Behaviour Confidence and Perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…This has significant implications for programs developing all students to be ready for further (undergraduate) study. Integral to these discussions are questions relating both to how universities can open access to students in ways that recognise and flex to accommodate prior educational disadvantage, but also support them to avoid unfulfilled expectations and 'unrealistic optimism' (Sanders et al, 2016) that consequently lead to attrition.…”
Section: Resultsmentioning
confidence: 99%
“…This has significant implications for programs developing all students to be ready for further (undergraduate) study. Integral to these discussions are questions relating both to how universities can open access to students in ways that recognise and flex to accommodate prior educational disadvantage, but also support them to avoid unfulfilled expectations and 'unrealistic optimism' (Sanders et al, 2016) that consequently lead to attrition.…”
Section: Resultsmentioning
confidence: 99%
“…Nicholson et al, 2013). These two measures, ABC and PEL, were found to be good predictors of successful completion of studies with foundation year students in a previous study (Sanders et al, 2016). (Foundation year programmes are one means by which students lacking the necessary qualifications or skills to enter HE can acquire those skills and improve their preparedness for degree-level study.)…”
Section: Detecting Uncertainty Predicting Outcomementioning
confidence: 92%
“…The aim of the study was to evaluate the use of these two psychometric measures at the start of the academic year for identifying students at risk of non-completion. Previously, three of the four subscales of the ABC (Studying, Grades and Attendance) have been shown to be predictive for all three years of an undergraduate psychology programme (Nicholson et al, 2013) and the Attendance subscale has been shown to predictive with foundation year students (Sanders et al, 2016). If these concise measures can be shown to be effective detectors of uncertainty and doubting at the start of the academic year, they could be used as routine screening for all new students enabling institutions to target interventions to improve retention.…”
Section: Detecting Uncertainty Predicting Outcomementioning
confidence: 99%
“…Various models have been built which both explain the observed retention for groups of students and which provide a basis for targeting additional support. New data is sometimes collected for use in predictive models but more usually existing registration data and data from a virtual learning environment data is used to identify students "at risk" (Sanders et al 2016;Rose-Adams 2013;Fowler&Norrie 2009;Essa&Ahad 2012 andSimpson et al 2006).…”
Section: Literature Reviewmentioning
confidence: 99%